EDUCATIVE POTENTIAL OF THE NEW TECHNOLOGIES - Delgado Santa Gadea, Kenneth (2014)
The new information and communication technologies differ from the traditional (cinema, newspaper, radio, television) because they are telematic due to digitalization and interactive opportunities. Technology is not only an information distribution channel, it is also a way to connect many people around the world at different time, places and cultures. In this case, there are new learning opportunities arise, but also learning again and delearning, within the permanent education process.